2014
DOI: 10.1002/lary.24705
|View full text |Cite
|
Sign up to set email alerts
|

Functional and quality-of-life outcomes of transoral robotic surgery for carcinoma of unknown primary

Abstract: Objectives/Hypothesis To determine speech, eating, aesthetics, social disruption, and overall quality-of-life outcomes over a year period in patients who underwent transoral robotic surgery as part of carcinoma of unknown primary diagnosis and treatment. Study Design Observational prospective study. Methods Twenty-two patients who underwent transoral robotic surgery for the management of carcinoma of unknown primary were included. Patients prospectively completed the Head and Neck Cancer Inventory during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 21 publications
(68 reference statements)
5
53
1
Order By: Relevance
“…The mean 15D score in this study was in the same range as shown in patients with colorectal [20] and prostate cancer [21]. Previous studies on oncologically treated head and neck cancer patients show that a decline in HRQoL is usually seen during the first 3 months after treatment onset, but it then gradually improves towards 12 months [8,22] and even 5 years after treatment patients are satisfied with their QoL [23]. This trend of improvement was also obvious in our study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The mean 15D score in this study was in the same range as shown in patients with colorectal [20] and prostate cancer [21]. Previous studies on oncologically treated head and neck cancer patients show that a decline in HRQoL is usually seen during the first 3 months after treatment onset, but it then gradually improves towards 12 months [8,22] and even 5 years after treatment patients are satisfied with their QoL [23]. This trend of improvement was also obvious in our study.…”
Section: Discussionsupporting
confidence: 85%
“…In their study, patients were recruited even after one completed survey at any point of treatment and therefore no knowledge of change in QoL during treatment was shown. On the other hand, Durmus et al [22] showed HPV status to be insignificant in relation to QoL. In our study, the HPV/p16 status was not available for all patients with oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…11,12 The survey also includes 3 global QOL scores. Scores for each domain range from 0 to 100, with 100 being the best functional outcome reported by the patient.…”
Section: Qol Assessmentmentioning
confidence: 99%
“…According to the review by Fu et al [43] the overall complication rate of TORS/TLM was low (7%), but not zero. Moreover, a significant decline in multiple QOL domains such as speech, eating, aesthetics, and social disruption has been recently demonstrated up to 12 months after TORS [47].…”
Section: Discussionmentioning
confidence: 99%